Using informed consent to save trust - Eyal, Nir (Journal of medical ethics, 2014)
Increasingly, bioethicists defend informed consent as a safeguard for trust in caretakers and medical institutions. This paper discusses an ‘ideal type’ of that move. What I call the trust-promotion argument for informed consent states: 1. Social trust, especially trust in caretakers and medical institutions, is necessary so that, for example, people seek medical advice, comply with it, and participate in medical research. 2. Therefore, it is usually wrong to jeopardise that trust. 3. Coercion, deception, manipulation and other violations of standard informed consent requirements seriously jeopardise that trust. 4. Thus, standard informed consent requirements are justified. This article describes the initial promise of this argument, then identifies challenges to it. As I show, the value of trust fails to account for some commonsense intuitions about informed consent. We should revise the argument, commonsense morality, or both.